Les archives du CBIP/CASIP et du COJASOR : des sources pour une histoire de la bienfaisance et de l’action sociale juives de 1809 à nos jours - Laure Politis (Les Cahiers de Framespa)
On January 1st 2000, two Jewish social associations, the CASIP (originally, the «Comité de Bienfaisance» founded in 1809) and the COJASOR (founded in 1945), merged and gave birth to the Fondation CASIP-COJASOR the goal of which is the social work in all its aspects. In the early 19th century, Napoleon 1st entrusted the «Consistoire de Paris» with two main assignments: the reform and centralizing of all the Jewish community’s welfare institutions. It led to the creation of the Comité de Bienfaisance Israélite de Paris (CBIP), in 1809. By the end of the 19th century, not only was the «Comité de Bienfaisance» supporting Parisian Jewish indigents but it also provided emergency assistance to the Eastern and Central European Jews. In the 50’s, the CBIP focused on the welcoming of north Africans immigrants while the COJASOR was bringing both material and moral helps to the Holocaust survivors. Today, the Fondation CASIP-COJASOR ensures the continuance of the goals of the founding associations. In 2005, the archives of the Fondation CASIP-COJASOR have been made available for consultation.